A mixed-method study to inform the design of a video observed therapy app to monitor individuals with TB in the Dominican Republic - Canario-Guzmán, Julio Arturo; Elias-Melgen, Ricardo; Mendoza, Eddys Rafael; Arias, Luis Felipe; Espinal, Roberto; Báez, Jeannette; Iribarren, Sarah (Frontiers in Public Health, 2025)
IntroductionVideo Observed-Therapy, a digital adherence technologies (DAT), could improve patients’ adherence to tuberculosis (TB) treatment. However, countries with high TB burden countries, such as the Dominican Republic, struggle to adopt DAT as a control and prevention tool to improve clinical outcomes. Objectives: To describe patients’ knowledge, attitudes and behaviors towards digital technologies for TB control and prevention in the Dominican Republic.MethodsA mixed-method study was implemented by organizing two Focus Group Discussions (FGDs) and a survey with 137 TB patients. Qualitative data were coded using the Integrated Behavior Model (IBM) and descriptive statistics were used to analyze knowledge, attitudes, practices, and preferences. Data integration was achieved by comparing convergent and divergent results.ResultsParticipants expressed a positive attitude towards using DAT to facilitate communication with health personnel to support treatment adherence. Participants noted the benefit of having an application that facilitates this process while safeguarding data privacy.ConclusionThis study demonstrates positive attitudes among individuals with TB toward adopting digital tools in their follow-up. Current practices suggest that intent to use DAT is prevalent, emphasizing the need to fully transition from intention to adoption of DAT to improve TB treatment outcomes.